Branding BRANDING STRATEGIES IN RISING THE NUMBER OF PARTNERS: BRANDING STRATEGIES TO IMPLEMENT ACCEPTION OF PARTNERS - FAUZIAH (Kindergarten: Jurnal Pendidikan Anak Usia Dini Indonesia, 2024)
Many educational institutions have emerged, giving rise to competition. To attract new students, educational institutions must find ways to attract students to their educational institutions. This research aims to find out what branding strategies can be carried out, how implementing branding strategies can increase the number of students, and what are the advantages of branding strategies implemented at the Mutiara Hati IT Kindergarten, Klaten, Central Java. The method used in this research is qualitative with a field research approach. The results of the research show that at the IT Mutiara Hati Kindergarten, Klaten, Central Java, the school's branding strategy uses digital marketing strategies. By using digital marketing strategies, we have succeeded in increasing the number of student. Using a digital marketing strategy has several advantages: it is easy, cheap, has a wide target reach, and can be targeted.